Pemikiran Filsafat Aristoteles Dalam Teologi Jabariyah - Irfan, Mohamad; Mutrofin, Mutrofin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This article aims to discuss the history of Jabariyah theology, figures, doctrines, and the influence of Aristotle's Ancient Greek philosophical thought in Jabariyah theology. The research method in this article is qualitative research using a library research approach. The data sources in this paper come from books and scientific journals that discuss the history and thought of Jabariyah theology and Aristotle's philosophical thought. The data collection technique used in this paper is done by reading, examining, and analyzing various literature related to Jabariyah and Aristotle's philosophical thought. The result of the discussion in this article is that the development of the Jabariyah group is closely related to the background of its founder, Ja'ad bin Dirham, who lived in Damascus, which is a Hellenistic center. The theological thinking adopted by Jabariyah in certain parts is influenced by Aristotle's philosophical thoughts such as the concept of first movers and the concept of determinism.